Agrobacterium tumefaciens fitness genes involved in the colonization of plant tumors and roots. Issue 2 (8th November 2021) - Torres, Marta; Jiquel, Audren; Jeanne, Etienne; Naquin, Delphine; Dessaux, Yves; Faure, Denis
Summary: Agrobacterium tumefaciens colonizes the galls (plant tumors) it causes, and the roots of host and nonhost plants. Transposon‐sequencing (Tn‐Seq) was used to discover A.tumefaciens genes involved in reproductive success (fitness genes) on Solanum lycopersicum and Populus trichocarpa tumors and S.lycopersicum and Zea mays roots. The identified fitness genes represent 3–8% of A. tumefaciens genes and contribute to carbon and nitrogen metabolism, synthesis and repair of DNA, RNA and proteins and envelope‐associated functions. Competition assays between 12 knockout mutants and wild‐type confirmed the involvement of 10 genes ( trpB, hisH, metH, cobN, ntrB, trxA, nrdJ, kamA, exoQ, wbbL ) in A.tumefaciens fitness under both tumor and root conditions. The remaining two genes ( fecA, noxA ) were important in tumors only. None of these mutants was nonpathogenic, but four ( hisH, trpB, exoQ, ntrB ) exhibited impaired virulence. Finally, we used this knowledge to search for chemical and biocontrol treatments that target some of the identified fitness pathways and report reduced tumorigenesis and impaired establishment of A.tumefaciens on tomato roots using tannic acid or Pseudomonas protegens, which affect iron assimilation. This work revealed A.tumefaciens pathways that contribute to its competitive survival in plants and highlights a strategy to identify plant protection approaches against this pathogen.